THE EFFECTIVENESS OF ANEMIA EDUCATION WITH AUDIOVISUAL MEDIA ON THE BEHAVIOR OF ADOLESCENT GIRLS CONSUMING IRON TABLETS - Christiana, Ester Christiana1; Pangaribuan, Maslan; Intarti, Wiwit Desi (Siklus : Journal Research Midwifery Politeknik Tegal, 2024)
Anemia in adolescents is a significant problem that occurs throughout the world. According to WHO (2018), the number of anemia sufferers among adolescent girls in the world is around 40-88%. Developing countries are around 53.7%. In Indonesia, 2018 32%, meaning 3-4 out of 10 adolescents suffer from anemia. In West Java, it reached 41.5%. Suboptimal nutritional intake habits and lack of physical activity influence this. This research aimed to determine the effectiveness of audiovisual media for anemia education and the behavior of adolescent girls who consume iron tablets. Research Design Pre-experimental one-group pretest-posttest. Population of adolescent girls, total sample 80 people, purposive sampling technique, standardized normality test, paired sample T-test hypothesis test. Results: Before receiving counseling on anemia through audiovisual media, the behavior of adolescent girls consuming iron tablets mostly fell in the poor category, namely 47 people (58.8%); after counseling, the behavior of adolescent girls consuming iron tablets was mostly the excellent category, namely 62 people (77.5%), Conclusion: Audio visual media is effective for educating about anemia on the behavior of adolescent girls consuming iron tablets, where the Sig value. (2-Tailed) 0.000 ( 0.05). The increase in behavior changes before and after counseling with audiovisual media was 19.68.